2006
DOI: 10.1029/2006gl026024
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol effects on the lifetime of shallow cumulus

Abstract: We explore the effects of increases in aerosol concentration on cloud lifetime for warm convective clouds using a two‐dimensional single cloud model and three‐dimensional large eddy simulations (LES). The models include size‐resolved treatment of drop size distributions and warm microphysical processes. It is shown using a variety of soundings representing marine trade cumulus, and continental convective clouds that contrary to expectation, an increase in aerosol concentration from very clean to very polluted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
193
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 195 publications
(202 citation statements)
references
References 17 publications
8
193
0
1
Order By: Relevance
“…The importance of such effects and the associated changes in cloud dynamics has been discussed by several authors (e.g. Jiang et al, 2006;Xue and Feingold, 2006). Recently, it has been suggested that for clouds with liquid water path less than about 50 g m −2 , the evaporation/condensation effect is of greater importance in controlling liquid water path than the precipitation suppression effect (Lee and Penner, 2011).…”
Section: Aerosol-cloud Interactions In Online Models With Prognostic mentioning
confidence: 99%
“…The importance of such effects and the associated changes in cloud dynamics has been discussed by several authors (e.g. Jiang et al, 2006;Xue and Feingold, 2006). Recently, it has been suggested that for clouds with liquid water path less than about 50 g m −2 , the evaporation/condensation effect is of greater importance in controlling liquid water path than the precipitation suppression effect (Lee and Penner, 2011).…”
Section: Aerosol-cloud Interactions In Online Models With Prognostic mentioning
confidence: 99%
“…An increase in CCN has also been suggested to enhance cloud lifetimes and liquid water path by lowering the collision-coalescence rate (Albrecht, 1989). This can, however, to some extent be offset by the moistening due to the suppression of precipitation (leading to increasing liquid water content and subsequent rain formation) and increased entrainment of environmental air (Ackerman et al, 2004;Xue and Feingold, 2006;Jiang et al, 2006;Altaratz et al, 2008). The effect of increased entrainment with increasing CCN is at present not taken into account in limited-resolution global models.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous completed studies attempt to understand aerosol effects on liquid phase clouds (e.g. Jiang et al, 2006;Lu and Seinfeld, 2005;Menon et al, 2008), less attention has been given to similar interactions in mixed-phase clouds (e.g. Lohmann and Diehl, 2006).…”
Section: Introductionmentioning
confidence: 99%